GDF15 is associated with thyroid cancer progression and may modulate thyroid cancer cell senescence in a p53-dependent manner - Ma, Jingyu; Liu, Zishuo; Hua, Rui; Ding, Changyuan; Yang, Zhenpeng; Liang, Weili; Lv, Bin (Frontiers in Endocrinology, 2025)
BackgroundThyroid cancer, the most prevalent endocrine malignancy, poses significant therapeutic challenges due to its heterogeneous biological behavior. Growth differentiation factor 15 (GDF15), a stress-responsive cytokine, is implicated in tumor progression and senescence regulation in various cancers. However, its role in thyroid cancer, particularly its interaction with the p53 signaling pathway, remains poorly understood. This study aimed to investigate the functional contribution of GDF15 to thyroid cancer progression and its regulatory mechanism in cancer cell senescence.MethodsPublic datasets and clinical specimens were analyzed to evaluate GDF15 expression patterns and their clinical significance. In vitro models were established using human thyroid cancer cell lines. GDF15 expression was modulated through siRNA-mediated silencing. RT-qPCR and Western blotting were employed to evaluate the expression levels of target molecules. Functional assays were conducted to assess proliferation (CCK-8, colony formation) and migration/invasion (transwell, cell scratch assay). Cellular senescence was evaluated by measuring β-galactosidase activity, γ-H2AX expression, and senescence-associated secretory phenotype factors. The dependency on p53 was elucidated through siRNA-mediated knockdown of p53. Mechanistic investigations were performed using RNA sequencing and Western blotting.ResultsCompared with adjacent normal tissues, GDF15 was significantly upregulated in thyroid cancer tissues and correlated with lymph node metastasis status. Knockdown of GDF15 suppressed proliferation, migration, and invasion while inducing cellular senescence. RNA sequencing revealed that GDF15 silencing activated the p53 signaling pathway and upregulated p53 expression. Rescue experiments utilizing p53 siRNA partially reversed GDF15-mediated senescence.ConclusionsGDF15 is implicated in the progression of thyroid cancer and potentially modulates cellular senescence through a p53-dependent mechanism, underscoring its dual functionality as both a pro-tumorigenic driver and a senescence regulator. These findings establish the potential of GDF15 as a therapeutic target and prognostic biomarker in thyroid cancer, providing novel insights developing senescence-centered therapeutic strategies.